Действие акустического излучения в вязкой жидкости на сферическую каплю идеальной жидкости - Гузь, А.Н.; Жук, А.П. (Прикладная механика, 2014)
Проведено дослідження дії радіаційної сили акустичного поля на сферичну краплю ідеальної рідини у в’язкій рідині. Одержано формули для обчислення величини радіаційної сили і напряму її дії. У випадку, коли зовнішня рідина ідеальна, чисельно досліджено залежність величини і напряму дії радіаційної сили від частоти, відношення густин та від адіабатичних модулів пружності зовнішньої рідини та рідини краплі. An action of the radiation force of acoustic field on the drop of ideal liquid, that is placed into the viscous liquid, is studied. The method is used, which is elaborated for the case of rigid particles. The formulas are obtained to calculate the value of radiation force and the direction of its action. In the case, when the external liquid is ideal, a dependence of the value and direction of action of radiation force on frequency, ratio of densities and adiabatic moduli of elasticity of the external liquid and drop liquid is studied numerically.